2018
DOI: 10.21608/mjcu.2018.56341
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Randomized Controlled Study Comparing Caudal Block versus Dorsal Penile Nerve Block as Postoperative Analgesia in Children Presented for Penile Surgery

Abstract: Background: Caudal block is recommended for analgesia during and after surface operation on the penis, for example circumcision and hypospadias repair. The aim of this study was to compare caudal block versus dorsal penile block in children undergoing penile surgery, regarding duration and quality of post-operative analgesia. Aim of the Study: To compare caudal block versus dorsal penile block in children undergoing penile surgery, our primary outcome was the duration of postoperative analgesia while our secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…In agreement with our work Yasser A. Ragheb et al,2018 [7] The Faces pain level was found to be substantially lower in the Caudal Group at 2H, 4H and 6H postoperative (p-value < 0.05) and the length of the block ranged from 1-5 hours in Penile Group and 1-10 hours in Caudal Group, with mean values of 2.57±1.10 hours and 6.07±2.10 hours respectively. A contrast between the two groups showed that there was a statistical change (p-value < 0.05) in the length of the block in the Caudal Group.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with our work Yasser A. Ragheb et al,2018 [7] The Faces pain level was found to be substantially lower in the Caudal Group at 2H, 4H and 6H postoperative (p-value < 0.05) and the length of the block ranged from 1-5 hours in Penile Group and 1-10 hours in Caudal Group, with mean values of 2.57±1.10 hours and 6.07±2.10 hours respectively. A contrast between the two groups showed that there was a statistical change (p-value < 0.05) in the length of the block in the Caudal Group.…”
Section: Discussionsupporting
confidence: 92%